Implementation of blended learning in professional development programmes for school principals: factors affecting the satisfaction of principals from disadvantaged areas in Vietnam. (3rd July 2022) - Tuan, Kim Manh; Hoan, Tran Huu; Hoang Yen, Duong Thi; Huyen, Nguyen Phuong
ABSTRACT: To support the implementation of Vietnam's new general education curriculum, Vietnam Ministry of Education and Training is organising a professional development programme integrating blended learning models for principals of general education institutions. In the period of educational reforms, there is a need for high-quality professional development for school principals. The satisfaction level of learners is an important indicator of the quality of a professional development programme. This study proposes a research model to analyse critical factors affecting the satisfaction of principals from disadvantaged areas in Vietnam with the professional development programme. In total, 1036 valid responses were received from 1096 principals (equivalent to 94.53%) of primary, secondary, and postsecondary schools in disadvantaged areas. The collected data set is then evaluated by exploratory factor analysis and regression analysis. The results show that all factors include learning objectives, course content, instructional methods, course assessment, technology support and organising and planning affect learners' satisfaction, however, at different levels. Organising and planning, course content and instructional methods are the three most influential factors positively affecting learners' satisfaction. Another finding is that non-minority groups are more satisfied with the programme than ethnic minority groups.